Pengaruh Implementasi Teknik Mind Mapping Terhadap Hasil Belajar Siswa Pada Mata Pelajaran Akidah Akhlak Di MAN 2 Payakumbuh - Nur Aziza; Muhiddinur Kamal; Zulfani Sesmiarni; Supratman Zakir (KOLONI, 2022)
This research is motivated by the many learning models proposed by education experts to realize the achievement of learning objectives. One of the learning models is the Mind Mapping learning model. Learning Akidah Akhlak at MAN 2 Payakumbuh, especially in class XI, uses a conventional learning model, namely a learning model that refers to the teacher in delivering learning, but it is not optimal. This can be seen from the low student learning outcomes. The average daily test scores of students have not reached the predetermined Minimum Completeness Criteria (KKM). The hypothesis in this study is that the learning outcomes of Akidah Akhlak using the Mind Mapping learning model are better than the learning outcomes of Akidah Akhlak using the conventional model at MAN 2 Payakumbuh. The type of this research is Quasy Experiment with pretest-post test control group design. The population in this study were students of class XI MIA totaling 138 people, consisting of 4 normal and homogeneous locales. The sample in this study was class XI MIA 3 as the experimental class and class XI MIA 1 as the control class. The data obtained from the results of this study were processed using the t-test, after the analysis obtained tcount = 5.7529 and ttable = 1.671093. Thus, it is obtained that tcount > ttable is 5.7529 and > 1.671093 at the real level = 0.05, meaning that the hypothesis is accepted. So it can be concluded that student learning outcomes using the Mind Mapping learning model are better than student learning outcomes using conventional learning models. Keywords: Mind Mapping, Learning Outcomes, Akidah Akhlak